MENINGKATKAN KETERAMPILAN BERBICARA MELALUI PENGGUNAAN SINIAR “DONGENG PAMAN GERY” PADA SISWA KELAS V SDN KRANJI V - Anisa Rahmawati; Anggi Citra Apriliana; Yofita Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This classroom action research aimed to improve fifth grade students’ speaking skills through the use of the “Dongeng Paman Gery” podcast at SDN Kranji V. The study was conducted in two cycles using the Kemmis and McTaggart model consisting of planning, action, observation, and reflection stages. The subjects were 35 fifth grade students. Data were collected through speaking performance tests, observation sheets, and documentation. The assessed speaking indicators included fluency and coherence, pronunciation and intonation, diction, and self-confidence. The results showed an improvement in students’ speaking skills after the implementation of the podcast media. Students became more confident, fluent, and structured in retelling stories orally. The use of audio podcast media provided authentic speaking models and increased student participation during learning activities. Therefore, the “Dongeng Paman Gery” podcast can be used as an innovative learning medium to improve elementary school students’ speaking skills.